2010
DOI: 10.1007/s12328-010-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of small flat early gastric cancer by flexible spectral imaging color enhancement

Abstract: Current conventional endoscopy often misses flat early gastric cancers (0-IIb) because they are sometimes invisible. We experienced a case of small flat early gastric cancer that had been missed by normal-caliber conventional endoscopy. By small-caliber endoscope, conventional endoscopy showed a subtle reddish change of gastric mucosa, but the image with flexible spectral imaging color enhancement clearly showed a flat reddish lesion with 10 mm diameter, distinct from the surrounding mucosa. Flat early gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Although there are no collected data regarding missed early gastric cancers, a case report was published about a flat cancer missed several times by per‐oral endoscopy with WLI alone and detected using a small‐caliber scope with FICE . Figure shows a cancer in the cardia missed by WLI with per‐oral endoscopy.…”
Section: Using Fice For Screening and Detailed Examinationsmentioning
confidence: 99%
“…Although there are no collected data regarding missed early gastric cancers, a case report was published about a flat cancer missed several times by per‐oral endoscopy with WLI alone and detected using a small‐caliber scope with FICE . Figure shows a cancer in the cardia missed by WLI with per‐oral endoscopy.…”
Section: Using Fice For Screening and Detailed Examinationsmentioning
confidence: 99%
“…Ultrathin endoscopy has been shown to result in poor visibility of malignant lesions in the proximal stomach using a xenon endoscope 9 , but not using laser endoscopy, although it has good visibility around the lesser curvature of the angle 28 29 . In this study, ultrathin LCI showed high visibility scores and significantly higher color differences in the proximal stomach compared with standard WLI.…”
Section: Discussionmentioning
confidence: 99%
“…LCI and BLI have been available with one small-caliber endoscope (e.g., EG-L580NW; Fujifilm Co.) using a laser endoscopic system since 2014 and with one (e.g., EG-740N; Fujifilm Co.) using an LED endoscopy system since 2018. These endoscopes are characterized by a small radius at the tip, which allows observation of upper gastrointestinal lesions with a frontal view [38,39]. A recent report showed that WLI using small-caliber endoscopy did not allow the diagnosis of a small red lesion as cancer, but BLI showed a discolored area around the red lesion with irregular vessels, resulting in the accurate diagnosis of an early case of gastric cancer [39].…”
Section: Stomachmentioning
confidence: 99%